Legal Malpractice Reflected In John Grisham's The Litigators Novel (2011): A Sociological Perspective - KHOTIMAH, Nurindah Khusnul, Dr. M. Thoyibi, M.S, Dr. Phil. Dewi Candraningrum, M.Ed (2015)
The major problem of the study is how legal malpractice is reflected in John Grisham's The Litigators novel (2011). The objectives of this study are (1) to describe the reality of American society in the late twentieth century and the early twenty-first century, (2) to identify the characteristics, causes, and effects of legal malpractice in John Grisham's The Litigators novel (2011), and (3) to reveal the relation between the novel and the reality of American society in the late twentieth century and early twenty-first century. In analyzing The Litigators novel, the writer uses descriptive qualitative research and sociological perspective. The primary data source is The Litigators novel (2011) and the secondary data sources are taken from some books, journals, articles and other matters that support this analysis. Data is used in this study is text of The Litigators novel. The technique of data collection is documentation and the technique of data analysis is descriptive analysis. Based on the analysis of all chapters, the writer finds characteristics, causes, and effects of legal malpractice. The things which are most talked about law because it is the major conflict in America by the late of twentieth and early twenty-first centuries. There are many forms of unlawful acts that were done by the lawyers because they want to be rich people. The unlawful acts include making false advertisement and testament, giving a lot of money to the regulatory agencies in order the cases run smoothly, and consuming alcohol, ect.